Management of public resources in disaster attention - UNGRD (2017)
The present essay tries to show the action of the UNGRD both administrative and financial, before the attention of emergencies and / or disasters at national level. In Colombia, emergencies and / or disasters are very frequent, since one does not end up attending one when another is already being presented. These events are mainly due to the geographic location of the country, the economic position of society, climate change Is being presented and other additional factors. In order to mitigate and attend to these events, the Presidency of the Republic created the National Unit for the Management of Disaster Risk - UNGRD as an entity attached to it, in order to direct disaster risk management and coordinate the operation of technical entities And operating systems that make up the National Disaster Risk Management System (SNGRD), based on a normative basis that would allow this in the development of its general purpose and to that stipulated in Decree 4147 of 2011 - By means of which Which is created - and Law 1523 of 2012 - By which the national disaster risk management policy is adopted and the National System of Disaster Risk Management is established. The UNGRD, when dealing with an emergency and / or disaster, administratively manages the different lines of action that are part of the Disaster Management Mission and in turn manages financially the special account of the Nation, created as financing mechanisms for Management Of Disaster Risk (National Fund for Disaster Risk Management - FNGRD).